2013
DOI: 10.1159/000354615
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein in Parkinson's Disease: Pathogenic Function and Translation into Animal Models

Abstract: Parkinson's disease is a common neurodegenerative disease characterised by the loss of dopaminergic neurons in the substantia nigra pars compacta and the formation of α-synuclein aggregates found in Lewy bodies throughout the brain. Several α-synuclein transgenic mouse models have been generated, as well as viral-mediated overexpression of wild-type and mutated α-synuclein to mimic the disease and to delineate the pathogenic pathway of α-synuclein-mediated toxicity and neurodegeneration. In this review, we wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 228 publications
(239 reference statements)
1
30
0
Order By: Relevance
“…Both a neurotoxic and a neuroprotective role for SNCA expression have been proposed in cell culture and animal models [26]. In addition, both up-regulation and down-regulation of SNCA expression in PD and control brains has been reported [6, 2729].…”
Section: Discussionmentioning
confidence: 99%
“…Both a neurotoxic and a neuroprotective role for SNCA expression have been proposed in cell culture and animal models [26]. In addition, both up-regulation and down-regulation of SNCA expression in PD and control brains has been reported [6, 2729].…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of the neurotoxic effects of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) provided a first viable model of the motor deficits of PD in primates. Although these and other experimental models suggested to shed light on the etiopathogenesis of PD and reproduced some key features of the disease, they did not succeed in reproducing both the pathology and progressive degenerative process in human PD [11]. However, circuitory loss and b-synchronization are shared by denervated animals and humans undergoing deep brain stimulation, and recent rotenone models combined with genetic PD models reproducing motor deficits, extranigral pathology and non-motor symptoms have shed light into the gen-environmental interactions [12].…”
mentioning
confidence: 92%
“…In PD, a-synuclein aggregates into Lewy bodies and conversion of a-synuclein from monomer to oligomeric form is a key event in the pathogenesis of PD [7]. aSynuclein is a 14.5-kDa protein and present at elevated levels in presynaptic nerve terminals in brain [8][9][10]. Barbour et al reported that the red blood cells are the major source of a-synuclein in blood [11].…”
Section: Introductionmentioning
confidence: 99%